Evaluation of heavy metals concentration in some mollusc species and human health risk in selected communities of Bakor sub-tribe, Ogoja, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The assessment of certain metals in the tissues of gastropods sourced from selected communities in Ogoja local government area was conducted between August and October 2024. Selected heavy metals, including As, Pb, Hg, Cd, Ni, and Zn, were analyzed using an Atomic Absorption Spectrophotometer. The analysis of heavy metal concentrations in A. marginata indicated that Zinc levels were the highest throughout the period. Similarly, V. contectus also exhibited the highest Zinc levels, with measurements of 3.1840 ± 0.24936 mg/kg in August and 3.3540 ± 0.24327 mg/kg in October. Statistical analysis demonstrated a significant difference (P < 0.05) between Zn and Ni compared to other metals across the species. The observed trend in mean heavy metal concentrations for A. marginata over the monthswas Zn > Ni > Cd > Pb > Hg > As. In contrast, V. contectus exhibited a different trend, with mean concentrations of Zn > Ni > Cd > Pb > As > Hg. It was also observed that the concentration of heavy metals in the aquatic snail V. contectus surpassed that of the land snail A. marginata. Consumers of gastropods, particularly A. marginata and V. contectus in Ogoja, should be informed through public awareness campaigns about the risks associated with consuming contaminated food due to the ongoing and indiscriminate disposal of waste in both aquatic and terrestrial environments.
Keywords: Archachatina marginata; Viviparus contectus; Lead (Pb); mercury (Hg); cadmium (Cd); zinc (Zn)